ANALISIS SWOT IMPLEMENTASI DIGITAL MARKETING PADA UMKM CATERING BUNDA NILA - Irmania Arida, Syiar; Renaldo, Riki (Jurnal TAM (Technology Acceptance Model), 2024)
This study aims to analyze the implementation of digital marketing in UMKM Catering Bunda Nila using a SWOT analysis approach. Digital marketing is an important strategy for UMKM in increasing market reach and competitiveness. The research method used is descriptive qualitative with data collection techniques through interviews, observations, documentation, and questionnaires. The results of the study indicate that in terms of strengths, UMKM Catering Bunda Nila has actively used social media such as Instagram and WhatsApp for marketing, has quality products at competitive prices, and gains customer loyalty from online promotion strategies. However, there are several weaknesses, such as lack of consistency in content creation, limited human resources who are experts in digital marketing, and less than optimal utilization of paid advertising features. In terms of opportunities, the rapid growth of digital marketing trends provides opportunities for UMKM to reach more customers, while the increasing use of food delivery services also supports digital marketing. On the other hand, the threats faced include tight competition with bigger competitors and changes in social media algorithms that can affect marketing reach. Based on the results of the SWOT analysis, this study recommends several digital marketing development strategies, such as increasing human resource capacity in content creation, optimizing the use of digital advertising, and utilizing various online marketing platforms to expand market reach. With the right strategy, UMKM Catering Bunda Nila can maximize digital marketing to increase its competitiveness in the culinary industry.